A Critical Appraisal of the Quality of Vertigo Practice Guidelines Using the AGREE II Tool: A EuroAIM Initiative. Issue 10 (10th December 2022) - Doniselli, Fabio Martino; Zanardo, Moreno; Mazon, Miguel; Cuccarini, Valeria; Rovira, Alex; Costa, Antonella; Sconfienza, Luca Maria; Arana, Estanislao
Abstract : Objectives: The aim of this review is to assess the methodological quality of guidelines for the management of vertigo and dizziness and to compare their recommendations, with specific focus on neuroimaging. Databases Reviewed: MEDLINE, EMBASE, National Guideline Clearinghouse, and National Institute for Health and Clinical Excellence database. Methods: In March 2022, a systematic search was performed to find practice guidelines of management of vertigo and dizziness. The evaluation of guidelines quality was performed independently by four authors using the AGREE II tool. We excluded from the results those guidelines that were not primarily focused on vertigo and dizziness, such as national/international guidelines in which vertigo and dizziness were only briefly mentioned. Results: Our strategy of literature search identified 161 studies, and 18 guidelines were selected for the appraisal. Only five guidelines reached the acceptance level in the overall result (at least 60%), with three of them reaching the highest scores (at least 80%). The highest scores were found in Domain 6 "Editorial Independence, " Domain 1 "Scope and purpose, " and Domain 4 "Clarity of presentation" (median value = 66%, 62%, and 61%, respectively). The remaining domains showed a low level of quality: Domain 2 "Stakeholder Involvement, " Domain 3 "Rigor of development, " and Domain 5 "Applicability" had median values of 27%, 27%, and 22%, respectively. The quality of these guidelines was very low, because of low involvement of multidisciplinary teams in writing guidelines recommendations. Conclusion: Considering all guidelines, only three had a "high" overall score, whereas 13 of 18 (72%) of them were rated as of "low" quality. Future guidelines might take this into account to improve clinical applicability.